Numerical simulation of vertical Bridgman solidification of CdZnTe - Jamai Hanen; Pateyron Bernard; Sammouda Habib; El Ganaoui M. (International Journal for Simulation and Multidisciplinary Design Optimization, 2014)
The solidification of the singular CdZnTe in axisymetric Vertical Bridgman (VB) cavity is investigated in the current study. The numerical approach is developed by using COMSOL Multiphysics software, which is based on finite elements method (FEM) with Arbitrary Lagrangian-Euleurian (ALE) formulation allowing treating the moving interface. Numerical aspects of different parameters that affect the solidification interface and present an important factor during the crystal growth’s process are presented and analyzed. Especial attention will be paid to investigate the thermophysical properties such as thermal diffusivity, heat capacity. Thermal conductivity and the effect of thermal condition specially the effect of cold temperature Tc which affects significantly the concavity and the convexity of the interface for specific ranges in the solidification of CdZnTe phenomena, but it is of great importance the crystal growth experts are not it given importance. It has been shown that this properties, the effect of Tc, and the variation of interface velocity affect the solid/liquid interface shape and the crystal growth process.